Pesquisa em educação ambiental e questões metodológicas: uma discussão coletiva - Reis, Marília Freitas de Campos Tozoni [UNESP]; Souza, Daniele Cristina de [UNESP] (Departamento de Educacao da Universidade Estadual Paulista – UNESP, 2014)
The Research on Environmental Education Meetings (EPEAs, in Portuguese) include in their schedule the Groups on Research Discussion (GDPs, in Portuguese). These are sessions to discuss and deepen themes considered significant to the research on environmental education but that must also be seen as a moment to gather the participation of researchers who present works related to the GDPs’ themes. The GDP on Methodological Questions happened during the VII EPEA in 2013 and conducted effusive discussions which resulted in the building of some indicators to be used in the research of our field in order to ensure more and more social commitment and scientific competence in the field's maturation process. This article presents part of these discussions with emphasis on those indicators.

Os Encontros de Pesquisa em Educação Ambiental – EPEAs – têm, em sua estrutura, os Grupos de Discussão de Pesquisa (GDPs). São sessões para discussão e aprofundamento de temas considerados significativos para a pesquisa em educação ambiental, mas que também devem ser consideradas um espaço de participação dos pesquisadores que apresentam trabalhos relacionados aos temas dos GDPs. O GDP Questões Metodológicas se reuniu no VII EPEA em 2013, empreendendo discussões acaloradas que resultaram na elaboração de alguns indicadores para a pesquisa em nosso campo garantir, cada vez mais, compromisso social e competência científica em seu processo de amadurecimento. Este artigo apresenta parte dessas discussões com ênfase nesses indicadores.
Research in environmental education and methodological issues: a collective discussion
Keywords: Research methodology; Epistemology; Educational phenomenon; Metodologia de pesquisa; Epistemologia; Fenômeno educativo